THE EFFECT OF ADVERTISING, PERCEIVED QUALITY AND BRAND AWARENESS ON CONSUMER PURCHASE INTENTION (CASE STUDY: ADIDAS SPORT SHOES) - Laluyan, Wanda Nadya; Pangemanan, Sifrid S.; Worang, Frederik G. (Universitas Sam Ratulangi, 2017)
ABSTRACT: Sports as needs, which is read by the companies manufacturers who produce a sport shoes product. In Indonesia, the competition in footwear industry is getting tight and variety. It makes so much many shoes retail opened and developing. With that situation, the companies are trying to create a variety shoes and trying to adding new value on their product to keep their customer and getting new consumers and of course to make them still survive in the market. The aims of this study are to analyze the effect of Advertising, Perceived Quality and Brand Awareness on Consumer Purchase Intention of Adidas Sport Shoes. This research is causal type of research which uses primary data obtained through questionnaires and uses multiple regression analysis. The population observed is people in Manado who have used Adidas Sport Shoes with 100 respondents as the sample size.Keywords: Advertising, Perceived Quality, Brand Awareness, Consumer Purchase Intention